The Influence of Automation in the Accounting Professsion in Mukono Central Division - Gerone Hannah Nabudde (Uganda Christian University, 2026)
Traditional methods of accounting are becoming a problem in the modern financial system despite the fact that they are the foundation of accounting. This study explains the influence of automation on the accounting profession mainly focusing on the difficulties related with manual accounting practices. To explore this change effectively, data collection was done with the use of a questionnaire given to different accounting professionals across different sectors. The findings show a very big change in the accounting profession where automation has changes accounting from manual record keeping to digitalization. Findings show that the major principles of accounting do not change but the accountant role is moving towards high data analysis levels. The study concludes that people are compliant and are adjusting to the shift in technology.
Undergraduate